Comparison of effects of two different feeding rations (high feed rates and limited) on growth of rainbow trout in rectangular concrete pools culture conditions of Susehri in Turkey - Seher Dirican; Haldun Musul (Kuwait Journal of Science)
This study is focused on comparison of effects of two different feeding rations on growth of rainbow trout in rectangular concrete pools culture conditions of Susehri in Turkey. Also, the water used in the experiment was analyzed for 15 physicochemical parameters. During the experiment, food was given to the fish in the first group at 2% ratio of their live weight and to the second group, until satiation. At the end of the experiment, the live weights of groups were determined as 116.3636.84 g, 147.5324.82 g, respectively and the difference among both groups have been found to be significant (P<0.05). In the study, total length gain, relative total length gain, weight gain, relative weight gain, specific growth rate, survival ratio, condition factor and feed conversion ratio of groups were calculated. Feed conversion rates have been found to be 1.57 and 2.93, respectively. The best feed conversion rate was found with the first group (2%). At the end of the economic analysis, it was found that food cost is low with the first group and high with the second group.